Preparation method of thermally driven Ce / Zr core-shell MOF catalytic material, catalytic material and application thereof

Through the preparation method of thermally driven Ce/Zr core-shell MOF catalytic material, the difficulties in taking into account both activity and stability of traditional MOF materials are solved, and efficient catalysis is achieved over a wide temperature range, and self-optimization and efficient oxygen vacancies are provided.

CN119733564APending Publication Date: 2025-04-01NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411808533.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Traditional single metal MOF materials often face problems that are difficult to take into account both activity and stability in practical applications, and the prior art is difficult to accurately regulate catalytic active sites, especially in a wide temperature range.

Method used

The preparation method of thermally driven Ce/Zr core-shell MOF catalytic material is adopted to construct the core-shell structures of the Ce-MOF core and Zr-MOF shell through a carefully designed step-by-step synthesis strategy, and the cerium ions are induced to release oxygen through the heat treatment activation process to form a dynamic catalytic active site.

Benefits of technology

It has achieved high activity and stability in a wide temperature range, has self-optimization ability, efficient oxygen vacancies generation, and good economic and sustainable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179935240000141
    Figure BDA0005179935240000141
  • Figure BDA0005179935240000142
    Figure BDA0005179935240000142
  • Figure BDA0005179935240000151
    Figure BDA0005179935240000151
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic materials, in particular to a preparation method of a thermally-driven Ce / Zr core-shell MOF catalytic material, the catalytic material and application of the catalytic material, and the preparation method comprises the following steps: (1) preparing a Ce-MOF core; (2) preparing a Zr-MOF shell layer on the basis of the Ce-MOF core; and (3) carrying out heat treatment activation on the obtained Ce / Zr core-shell MOF material: firstly, successfully constructing a core-shell structure of a Ce-MOF core and a Zr-MOF shell layer through an elaborately designed step-by-step synthesis strategy, and realizing functional separation and performance optimization. Secondly, cerium ions are induced to release oxygen at a high temperature by utilizing a heat treatment activation process, and a reversibly migrated oxygen vacancy is formed, so that a dynamic catalytic active site is created. And thirdly, a stress field formed at a core-shell interface regulates and controls metal-ligand interaction, so that the catalytic activity and stability of the material are further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic materials, and in particular to a preparation method of a driven Ce / Zr core-shell MOF catalytic material, a catalytic material and applications thereof. Background Art

[0002] In recent years, with the increasingly severe environmental problems and the growing demand for energy conversion, the development of efficient and stable multifunctional catalytic materials has become a research hotspot in the fields of materials science and catalytic chemistry. Metal-organic framework (MOF) materials have attracted extensive attention due to their high specific surface area, adjustable pore structure and diverse functionalization methods. However, traditional single metal MOF materials often face the problem of balancing activity and stability in practical applications.

[0003] At present, researchers have tried to improve the catalytic performance of MOF materials by mixing metal MOFs and loading precious metal nanoparticles. For example, some researchers prepared bimetallic MOFs by mixing cerium and zirconium, trying to combine the redox properties of cerium and the structural stability of zirconium. Other scholars have used post-synthesis modification methods to load platinum or palladium nanoparticles on the surface of MOF to improve catalytic activity. However, these methods still have some limitations: it is difficult to precisely control the metal distribution in mixed metal MOFs, and the loading of precious metals greatly increases the material cost.

[0004] In addition, most existing MOF catalytic materials lack the ability to precisely regulate catalytic active sites. In practical applications, catalysts often need to maintain high activity and stability at different temperatures, which places higher demands on the design of materials. Therefore, the development of MOF materials that can maintain high activity and stability over a wide temperature range and have adjustable catalytic active sites has important scientific significance and application value. Summary of the invention

[0005] The thermally driven Ce / Zr core-shell MOF catalytic material and its preparation method proposed in the present invention are designed to address the above-mentioned problems. The material adopts a unique core-shell structure design, which cleverly combines the high catalytic activity of cerium-based MOF and the excellent stability of zirconium-based MOF. More importantly, by introducing a thermally driven mechanism, dynamic regulation of catalytic active sites is achieved, which is not possible with existing technologies.

[0006] The object of the present invention is to provide a method for preparing a thermally driven Ce / Zr core-shell MOF catalytic material, comprising the following steps:

[0007] (1) Preparation of Ce-MOF core;

[0008] (2) preparing a Zr-MOF shell based on the Ce-MOF core;

[0009] (3) The obtained Ce / Zr core-shell MOF material is activated by heat treatment.

[0010] Preferably, the step (1) comprises:

[0011] First, 10-50 parts by weight of cerium (III) nitrate hexahydrate and 5-25 parts by weight of 1,3,5-benzenetricarboxylic acid are dissolved in 200-400 parts by weight of N,N-dimethylformamide;

[0012] Secondly, the resulting mixture is reacted at 140-180° C. for 12-48 hours;

[0013] Then, it was cooled to room temperature and the product was collected by centrifugation;

[0014] Again, wash with N,N-dimethylformamide and anhydrous ethanol three times respectively;

[0015] Finally, the Ce-MOF core material was obtained by vacuum drying at 60-80 °C for 12-24 h.

[0016] Preferably, the step (2) comprises:

[0017] First, 5-25 parts by weight of zirconium (IV) chloride and 3-15 parts by weight of terephthalic acid are dissolved in 100-200 parts by weight of N,N-dimethylformamide and 10-30 parts by weight of glacial acetic acid;

[0018] Secondly, adding 10-50 parts by weight of Ce-MOF core material to the obtained mixture;

[0019] Then, the resulting mixture is reacted at 120-160° C. for 24-72 hours;

[0020] Again, cool to room temperature and collect the product by centrifugation;

[0021] Finally, the mixture was washed with N,N-dimethylformamide and anhydrous ethanol for three times respectively and vacuum dried at 60-80°C for 12-24 hours to obtain the Ce / Zr core-shell MOF material.

[0022] Preferably, the step (3) comprises:

[0023] The obtained Ce / Zr core-shell MOF material was placed in a tubular furnace, and heated to 300-500°C at a heating rate of 2-5°C / min under a nitrogen atmosphere, maintained for 2-6 hours, and then naturally cooled to room temperature.

[0024] The thermally driven Ce / Zr core-shell MOF catalytic material prepared by the preparation method.

[0025] A thermally driven Ce / Zr core-shell MOF catalytic material, wherein the Ce-MOF core is prepared by reacting cerium (III) nitrate hexahydrate and 1,3,5-benzenetricarboxylic acid.

[0026] Preferably, the Zr-MOF shell is prepared by reacting zirconium (IV) chloride and terephthalic acid.

[0027] Preferably, the material has a core-shell structure, wherein Ce-MOF serves as the core and Zr-MOF serves as the shell.

[0028] Preferably, the material is activated by heat treatment at 300-500° C. for 2-6 hours.

[0029] The application of the thermally driven Ce / Zr core-shell MOF catalytic material in environmental catalysis, energy conversion or selective oxidation reaction.

[0030] The core innovation of the present invention is that: first, through a carefully designed step-by-step synthesis strategy, a core-shell structure of Ce-MOF core and Zr-MOF shell was successfully constructed, achieving functional separation and performance optimization. Secondly, by utilizing the heat treatment activation process, cerium ions were induced to release oxygen at high temperatures to form reversibly migrated oxygen vacancies, thereby creating dynamic catalytic active sites. Thirdly, the stress field formed at the core-shell interface regulates the metal-ligand interaction, further enhancing the catalytic activity and stability of the material.

[0031] From the perspective of chemical mechanism, the uniqueness of the present invention lies in the use of the variable valence state of cerium ions (Ce 3+ / Ce 4+ ) and the stable valence state of zirconium ions (Zr 4+ ) in the thermally driven process. 4+ Restore to Ce 3+ , while releasing oxygen to form oxygen vacancies. These oxygen vacancies are not only important catalytic active sites, but can also migrate in the material, achieving a dynamic distribution of active sites. The zirconium-based MOF shell provides excellent structural stability through its strongly bonded Zr-OC structure, and may also participate in the electron transfer process, further enhancing the catalytic performance.

[0032] From the perspective of molecular orbital theory, Ce 3+ The interaction between the 4f orbital of O and the O 2p orbital may play a key role in the catalytic process. The formation of oxygen vacancies changes the local electronic structure and may reduce the adsorption and activation energy barriers of reactant molecules. At the same time, the stress field at the core-shell interface may lead to slight changes in the coordination environment around the metal center, optimizing the electronic structure of the catalytic active site.

[0033] The beneficial effects of the present invention are mainly reflected in the following aspects:

[0034] 1. High catalytic activity: Through the core-shell structure design and thermal drive mechanism, it achieves excellent catalytic performance of 50% CO conversion rate at low temperature (such as 95°C).

[0035] 2. Excellent stability: After 100 hours of high-temperature reaction, it can still maintain 98% of its initial activity, showing thermal stability far exceeding that of conventional MOF materials.

[0036] 3. Wide temperature adaptability: It exhibits excellent catalytic performance in a wide range from room temperature to 300°C, meeting the needs of different application scenarios.

[0037] 4. Self-optimization capability: The active self-optimization phenomenon exhibited during the thermal cycle process provides the possibility for long-term use.

[0038] 5. Efficient oxygen vacancy generation: The significant increase in oxygen vacancy concentration (up to 94.4%) after heat treatment provides a large number of active sites for catalytic reactions.

[0039] 6. Environmentally friendly: Compared with traditional precious metal catalysts, the cerium and zirconium used in the present invention are both relatively abundant elements in the earth's crust and have good economy and sustainability.

[0040] In general, the thermally driven Ce / Zr core-shell MOF catalytic material proposed in this invention not only solves many challenges faced by traditional MOF materials in practical applications, but also achieves some unexpected performance advantages through ingenious structural design and mechanism innovation. This provides new ideas and directions for the development of a new generation of efficient, stable and multifunctional catalytic materials, and is expected to play an important role in environmental governance, energy conversion, fine chemicals and other fields. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] This embodiment provides a method for preparing a thermally driven Ce / Zr core-shell MOF catalytic material, comprising the following steps:

[0044] (1) Preparation of Ce-MOF core:

[0045] First, 10 parts by weight of cerium (III) nitrate hexahydrate and 5 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 200 parts by weight of N,N-dimethylformamide. Secondly, the resulting mixture was transferred to an autoclave and reacted at 140°C for 12 hours. Then, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 3000rpm for 10 minutes. Again, it was washed 3 times with N,N-dimethylformamide and anhydrous ethanol respectively. Finally, it was vacuum dried at 60°C for 12 hours to obtain the Ce-MOF core material.

[0046] (2) Preparation of Zr-MOF shell:

[0047] First, 5 parts by weight of zirconium (IV) chloride and 3 parts by weight of terephthalic acid were dissolved in 100 parts by weight of N, N-dimethylformamide and 10 parts by weight of glacial acetic acid. Secondly, 10 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 120°C for 24 hours. Again, the reaction product was naturally cooled to room temperature, and the product was collected by centrifugation at 3000rpm for 10 minutes. Finally, it was washed 3 times with N, N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 60°C for 12 hours to obtain Ce / Zr core-shell MOF material.

[0048] (3) Heat treatment activation:

[0049] The obtained Ce / Zr core-shell MOF material was placed in a tubular furnace, and heated to 300°C at a heating rate of 2°C / min under a nitrogen atmosphere, maintained for 2 hours, and then naturally cooled to room temperature to obtain a heat-driven Ce / Zr core-shell MOF catalytic material.

[0050] Preferably, in an embodiment of the present invention, the Ce-MOF core is prepared by reacting cerium (III) nitrate hexahydrate and 1,3,5-benzenetricarboxylic acid. This selection can make the core material have good oxygen vacancy generation ability, which is beneficial to improve the catalytic activity of the material. At the same time, 1,3,5-benzenetricarboxylic acid as an organic ligand can provide a stable porous structure, increase the specific surface area of ​​the material, and thus improve the catalytic efficiency.

[0051] Example 2

[0052] This embodiment provides a method for preparing another heat-driven Ce / Zr core-shell MOF catalytic material, comprising the following steps:

[0053] (1) Preparation of Ce-MOF core:

[0054] First, 30 parts by weight of cerium (III) nitrate hexahydrate and 15 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 300 parts by weight of N,N-dimethylformamide. Secondly, the resulting mixture was transferred to an autoclave and reacted at 160°C for 30 hours. Then, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 4000rpm for 15 minutes. Again, it was washed 3 times with N,N-dimethylformamide and anhydrous ethanol respectively. Finally, it was vacuum dried at 70°C for 18 hours to obtain the Ce-MOF core material.

[0055] (2) Preparation of Zr-MOF shell:

[0056] First, 15 parts by weight of zirconium (IV) chloride and 9 parts by weight of terephthalic acid were dissolved in 150 parts by weight of N, N-dimethylformamide and 20 parts by weight of glacial acetic acid. Secondly, 30 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 140°C for 48 hours. Again, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 4000rpm for 15 minutes. Finally, it was washed 3 times with N, N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 70°C for 18 hours to obtain Ce / Zr core-shell MOF material.

[0057] (3) Heat treatment activation:

[0058] The obtained Ce / Zr core-shell MOF material was placed in a tubular furnace, and heated to 400°C at a heating rate of 3.5°C / min under a nitrogen atmosphere, maintained for 4 hours, and then naturally cooled to room temperature to obtain a heat-driven Ce / Zr core-shell MOF catalytic material.

[0059] Preferably, in an embodiment of the present invention, the Zr-MOF shell is prepared by reacting zirconium (IV) chloride and terephthalic acid. This selection can make the shell material have good structural stability, which is beneficial to protect the core structure and prolong the life of the catalyst. At the same time, terephthalic acid as an organic ligand can provide an appropriate pore structure, which is convenient for the diffusion of reactants and products, thereby improving the catalytic efficiency.

[0060] Example 3

[0061] This embodiment provides a method for preparing a thermally driven Ce / Zr core-shell MOF catalytic material, comprising the following steps:

[0062] (1) Preparation of Ce-MOF core:

[0063] First, 50 parts by weight of cerium (III) nitrate hexahydrate and 25 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 400 parts by weight of N,N-dimethylformamide. Secondly, the resulting mixture was transferred to an autoclave and reacted at 180°C for 48 hours. Then, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 5000rpm for 20 minutes. Again, it was washed 3 times with N,N-dimethylformamide and anhydrous ethanol respectively. Finally, it was vacuum dried at 80°C for 24 hours to obtain the Ce-MOF core material.

[0064] (2) Preparation of Zr-MOF shell:

[0065] First, 25 parts by weight of zirconium (IV) chloride and 15 parts by weight of terephthalic acid were dissolved in 200 parts by weight of N, N-dimethylformamide and 30 parts by weight of glacial acetic acid. Secondly, 50 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 160°C for 72 hours. Again, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 5000rpm for 20 minutes. Finally, it was washed 3 times with N, N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 80°C for 24 hours to obtain Ce / Zr core-shell MOF material.

[0066] (3) Heat treatment activation:

[0067] The obtained Ce / Zr core-shell MOF material was placed in a tubular furnace, and heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere, maintained for 6 hours, and then naturally cooled to room temperature to obtain a heat-driven Ce / Zr core-shell MOF catalytic material.

[0068] Preferably, in an embodiment of the present invention, the material has a core-shell structure, wherein Ce-MOF is the core and Zr-MOF is the shell. This unique core-shell structure design can achieve functional separation, the Ce-MOF core is mainly responsible for providing catalytic active sites, and the Zr-MOF shell provides structural stability. This structural design solves the technical contradiction that traditional single metal MOF materials are difficult to balance activity and stability, and can also regulate metal-ligand interactions through interfacial effects to further enhance the catalytic performance of the material.

[0069] Example 4

[0070] This embodiment provides a method for preparing a thermally driven Ce / Zr core-shell MOF catalytic material, comprising the following steps:

[0071] (1) Preparation of Ce-MOF core:

[0072] First, 40 parts by weight of cerium (III) nitrate hexahydrate and 20 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 350 parts by weight of N,N-dimethylformamide. Secondly, the resulting mixture was transferred to an autoclave and reacted at 170°C for 36 hours. Then, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 4500rpm for 18 minutes. Again, it was washed 3 times with N,N-dimethylformamide and anhydrous ethanol respectively. Finally, it was vacuum dried at 75°C for 20 hours to obtain the Ce-MOF core material.

[0073] (2) Preparation of Zr-MOF shell:

[0074] First, 20 parts by weight of zirconium (IV) chloride and 12 parts by weight of terephthalic acid were dissolved in 175 parts by weight of N, N-dimethylformamide and 25 parts by weight of glacial acetic acid. Secondly, 40 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 150°C for 60 hours. Again, the reaction product was naturally cooled to room temperature, and the product was collected by centrifugation at 4500rpm for 18 minutes. Finally, it was washed 3 times with N, N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 75°C for 20 hours to obtain Ce / Zr core-shell MOF material.

[0075] (3) Heat treatment activation:

[0076] The obtained Ce / Zr core-shell MOF material was placed in a tubular furnace, and heated to 450°C at a heating rate of 4°C / min under a nitrogen atmosphere, maintained for 5 hours, and then naturally cooled to room temperature to obtain a heat-driven Ce / Zr core-shell MOF catalytic material.

[0077] Preferably, in an embodiment of the present invention, the material is activated by heat treatment and treated at 300-500°C for 2-6 hours. This heat treatment process is crucial to the performance of the material. First, it can release oxygen vacancies from the cerium-based core at high temperatures. These oxygen vacancies are important catalytic active sites and can participate in a variety of redox reactions. Secondly, the heat treatment process can achieve reversible migration of oxygen vacancies, forming dynamic catalytic active sites, which increases the efficiency of the catalytic process. Finally, the heat treatment may also affect the flexibility and pore structure of the MOF skeleton, thereby having a multi-faceted impact on the entire catalytic process.

[0078] Through the above four embodiments, we can see that the heat-driven Ce / Zr core-shell MOF catalytic material and its preparation method of the present invention have broad application prospects. The material can play an important role in environmental catalysis, energy conversion or selective oxidation reaction. For example, it has potential application value in the fields of automobile exhaust purification, VOCs degradation, low-temperature water vapor shift reaction, methanol reforming hydrogen production, alcohols selective oxidation, partial oxidation of alkanes, etc. This versatility stems from the unique core-shell structure design and heat-driven mechanism of the material, which enables it to maintain high catalytic activity while also having excellent stability and controllability, providing new ideas and directions for the design of MOF catalytic materials.

[0079] Comparative Example 1: Single Ce-MOF Material

[0080] This comparative example is intended to verify the importance of the core-shell structure and is compared with Example 1. The preparation method is as follows:

[0081] (1) Preparation of Ce-MOF materials:

[0082] First, 10 parts by weight of cerium (III) nitrate hexahydrate and 5 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 200 parts by weight of N,N-dimethylformamide. Secondly, the resulting mixture was transferred to an autoclave and reacted at 140°C for 12 hours. Then, the reaction product was naturally cooled to room temperature and the product was collected by centrifugation at 3000rpm for 10 minutes. Again, it was washed 3 times with N,N-dimethylformamide and anhydrous ethanol respectively. Finally, it was vacuum dried at 60°C for 12 hours to obtain Ce-MOF material.

[0083] (2) Heat treatment activation:

[0084] The obtained Ce-MOF material was placed in a tubular furnace, and heated to 300°C at a heating rate of 2°C / min under a nitrogen atmosphere, maintained for 2 hours, and then naturally cooled to room temperature to obtain a heat-treated Ce-MOF catalytic material.

[0085] By comparing the catalytic performance of Ce-MOF single material and Ce / Zr core-shell MOF material, we can verify the important role of core-shell structure in improving material stability and catalytic activity.

[0086] Comparative Example 2: Ce / Zr core-shell MOF material without heat treatment

[0087] This comparative example is intended to verify the necessity of heat treatment activation and is compared with Example 2. The preparation method is as follows:

[0088] (1) Preparation of Ce-MOF core:

[0089] Same as step (1) of Example 2.

[0090] (2) Preparation of Zr-MOF shell:

[0091] Same as step (2) of Example 2.

[0092] This comparative example omits the heat treatment activation step and directly obtains the Ce / Zr core-shell MOF material. By comparing the catalytic performance of the material before and after heat treatment, we can demonstrate the key role of the thermal driving mechanism in the formation of dynamic catalytic active sites.

[0093] Comparative Example 3: Core-shell MOF material with high Ce / Zr ratio

[0094] This comparative example is intended to verify the importance of the ratio of Ce to Zr and is compared with Example 3. The preparation method is as follows:

[0095] (1) Preparation of Ce-MOF core:

[0096] Same as step (1) of Example 3.

[0097] (2) Preparation of Zr-MOF shell:

[0098] First, 10 parts by weight of zirconium (IV) chloride and 6 parts by weight of terephthalic acid were dissolved in 200 parts by weight of N, N-dimethylformamide and 30 parts by weight of glacial acetic acid. Secondly, 50 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 160°C for 72 hours. Again, the reaction product was naturally cooled to room temperature, and the product was collected by centrifugation at 5000rpm for 20 minutes. Finally, it was washed 3 times with N, N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 80°C for 24 hours to obtain Ce / Zr core-shell MOF material.

[0099] (3) Heat treatment activation:

[0100] Same as step (3) of Example 3.

[0101] By comparing the material properties of different Ce / Zr ratios, we can demonstrate the influence of the synergistic effect of Ce and Zr on the catalytic performance in the present invention.

[0102] Comparative Example 4: Ce / Zr core-shell MOF materials using different organic ligands

[0103] This comparative example is intended to verify the importance of organic ligand selection and is compared with Example 4. The preparation method is as follows:

[0104] (1) Preparation of Ce-MOF core:

[0105] First, 40 parts by weight of cerium (III) nitrate hexahydrate and 20 parts by weight of terephthalic acid were dissolved in 350 parts by weight of N, N-dimethylformamide. Secondly, the resulting mixture was transferred to an autoclave and reacted at 170°C for 36 hours. Then, the reaction product was naturally cooled to room temperature and collected by centrifugation at 4500rpm for 18 minutes. Again, it was washed 3 times with N, N-dimethylformamide and anhydrous ethanol respectively. Finally, it was vacuum dried at 75°C for 20 hours to obtain the Ce-MOF core material.

[0106] (2) Preparation of Zr-MOF shell:

[0107] First, 20 parts by weight of zirconium (IV) chloride and 12 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 175 parts by weight of N,N-dimethylformamide and 25 parts by weight of glacial acetic acid. Secondly, 40 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 150°C for 60 hours. Again, the reaction product was naturally cooled to room temperature, and the product was collected by centrifugation at 4500rpm for 18 minutes. Finally, it was washed 3 times with N,N-dimethylformamide and anhydrous ethanol respectively, and vacuum dried at 75°C for 20 hours to obtain Ce / Zr core-shell MOF material.

[0108] (3) Heat treatment activation:

[0109] Same as step (3) of Example 4.

[0110] By comparing the material properties of different organic ligand combinations, we can demonstrate the importance of the selected organic ligands in the present invention for the formation of the ideal porous structure and catalytic activity.

[0111] Comparative Example 5: Low-temperature synthesized Ce / Zr core-shell MOF material

[0112] This comparative example is intended to verify the importance of synthesis temperature and is compared with Example 1. The preparation method is as follows:

[0113] (1) Preparation of Ce-MOF core:

[0114] First, 10 parts by weight of cerium (III) nitrate hexahydrate and 5 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 200 parts by weight of N,N-dimethylformamide. Then, the resulting mixture was transferred to an autoclave and reacted at 100° C. for 12 hours. The subsequent steps were the same as step (1) of Example 1.

[0115] (2) Preparation of Zr-MOF shell:

[0116] First, 5 parts by weight of zirconium (IV) chloride and 3 parts by weight of terephthalic acid were dissolved in 100 parts by weight of N,N-dimethylformamide and 10 parts by weight of glacial acetic acid. Next, 10 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 80°C for 24 hours. The subsequent steps were the same as step (2) of Example 1.

[0117] (3) Heat treatment activation:

[0118] Same as step (3) of Example 1.

[0119] By comparing the properties of materials prepared at different synthesis temperatures, we can demonstrate the importance of the synthesis temperature selected in the present invention for forming an ideal crystal structure and core-shell structure.

[0120] Comparative Example 6: Ce / Zr core-shell MOF material synthesized in a short time

[0121] This comparative example is intended to verify the importance of synthesis time and is compared with Example 2. The preparation method is as follows:

[0122] (1) Preparation of Ce-MOF core:

[0123] First, 30 parts by weight of cerium (III) nitrate hexahydrate and 15 parts by weight of 1,3,5-benzenetricarboxylic acid were dissolved in 300 parts by weight of N,N-dimethylformamide. Then, the resulting mixture was transferred to an autoclave and reacted at 160° C. for 6 hours. The subsequent steps were the same as step (1) of Example 2.

[0124] (2) Preparation of Zr-MOF shell:

[0125] First, 15 parts by weight of zirconium (IV) chloride and 9 parts by weight of terephthalic acid were dissolved in 150 parts by weight of N,N-dimethylformamide and 20 parts by weight of glacial acetic acid. Next, 30 parts by weight of Ce-MOF core material were added to the resulting mixture. Then, the resulting mixture was transferred to an autoclave and reacted at 140°C for 12 hours. The subsequent steps were the same as step (2) of Example 2.

[0126] (3) Heat treatment activation:

[0127] Same as step (3) of Example 2.

[0128] By comparing the properties of materials prepared with different synthesis times, we can demonstrate the importance of the synthesis time selected in the present invention for forming a complete core-shell structure and an ideal crystal morphology.

[0129] Through these six comparative examples, we have fully verified the importance of key factors such as core-shell structure design, heat treatment activation, metal ratio, organic ligand selection, synthesis temperature and time in the present invention for the preparation of high-performance heat-driven Ce / Zr core-shell MOF catalytic materials. These comparative experiments not only cover the various technical features of the present invention, but also reflect the synergistic effect between these features, fully demonstrating the creativity and superiority of the present invention.

[0130] In order to comprehensively evaluate the performance and superiority of the thermally driven Ce / Zr core-shell MOF catalytic material of the present invention, we designed a series of test experiments covering the structural characteristics, catalytic performance, stability and thermal driving characteristics of the material. These experiments are intended to verify the core innovations of the present invention, including core-shell structure design, thermal driving mechanism, and the synergistic effect of Ce and Zr.

[0131] Experiment 1: Structural representation

[0132] Experimental conditions:

[0133] 1. X-ray diffraction (XRD): using Rigaku Ultima IV diffractometer, Cu Kα radiation The scanning range was 2θ=5-50°, and the scanning rate was 2° / min.

[0134] 2. Scanning electron microscopy (SEM): A JEOL JSM-7600F field emission scanning electron microscope was used with an accelerating voltage of 5 kV.

[0135] 3. Transmission electron microscopy (TEM): A FEI Tecnai G2 F20 transmission electron microscope was used with an accelerating voltage of 200 kV.

[0136] 4. Nitrogen adsorption and desorption: Micromeritics ASAP 2020 surface area and porosity analyzer was used, and the test temperature was 77K.

[0137] Experimental methods:

[0138] First, the samples were ground into fine powder. For XRD test, the powder samples were pressed into thin sheets. For SEM observation, the samples were dispersed on conductive tape. For TEM observation, the samples were dispersed in ethanol and dropped onto a copper grid after ultrasonic treatment. For nitrogen adsorption-desorption test, vacuum degassing was performed at 150 °C for 12 h.

[0139] Table 1: Structural characterization results

[0140] sample Crystalline purity (%) Average particle size (nm) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Example 1 98.5 120 1250 0.82 Example 2 99.1 150 1380 0.95 Example 3 99.3 180 1520 1.08 Example 4 98.9 160 1450 1.02 Comparative Example 1 97.8 100 980 0.65 Comparative Example 2 98.7 155 1320 0.91 Comparative Example 3 98.2 170 1400 0.98 Comparative Example 4 97.5 145 1280 0.88 Comparative Example 5 96.8 90 850 0.58 Comparative Example 6 97.2 130 1100 0.76

[0141] Experiment 2: Catalytic performance evaluation

[0142] Experimental conditions:

[0143] CO oxidation reaction was selected as the model reaction. A fixed bed microreactor was used, the catalyst dosage was 100 mg, the reaction gas was a mixture of 1% CO / He and 20% O2 / He, and the total flow rate was 50 mL / min. The reaction temperature range was 25-300°C, and the product composition was analyzed online using a gas chromatograph (equipped with a TCD detector).

[0144] Experimental methods:

[0145] First, the catalyst was loaded into a quartz reaction tube. Then, the temperature was raised to 300°C in a He atmosphere and kept for 1 hour for pretreatment. Next, the reaction gas was switched and the temperature was lowered to room temperature at a rate of 5°C / min. Finally, the temperature was raised to 300°C at a rate of 2°C / min, and a data point was taken every 25°C.

[0146] Table 2: CO oxidation reaction performance

[0147]

[0148] Note: 50 and T 90 They represent the temperatures when the CO conversion rate reaches 50% and 90%, respectively.

[0149] Experiment 3: Thermal stability and cycle performance test

[0150] Experimental conditions:

[0151] The same reaction apparatus as in Experiment 2 was used. The catalyst was subjected to CO oxidation reaction at 200°C for 100 hours. The catalytic activity was measured every 10 hours. The cycle test included 5 heating and cooling cycles, with the temperature range of each cycle being 25-300°C.

[0152] Experimental methods:

[0153] First, the catalyst was loaded into the reactor and pretreated. Then, the temperature was adjusted to 200°C to start the long-term stability test. For the cycle test, the temperature was cycled between 25-300°C at a rate of 5°C / min, and the catalytic activity at room temperature was measured after each cycle.

[0154] Table 3: Thermal stability and cycling performance results

[0155]

[0156]

[0157] Experiment 4: In situ XPS analysis

[0158] Experimental conditions:

[0159] Thermo Scientific K-Alpha+ in-situ XPS system was used, with an Al Kα X-ray source (1486.6 eV) and a vacuum better than 1×10 -9 The sample is pretreated and oxidized to CO in the reaction chamber at a temperature ranging from 25 to 300 °C.

[0160] Experimental methods:

[0161] First, the sample was pressed into a thin sheet and fixed on a sample stage. Then, the sample was pretreated under ultra-high vacuum. Next, CO oxidation reaction was carried out at different temperatures, and XPS spectra were collected simultaneously. The Ce 3d and O1s spectral regions were focused on to analyze the valence state changes of Ce and the formation of oxygen vacancies.

[0162] Table 4: In situ XPS analysis results

[0163]

[0164] Based on the above experimental results, we can draw the following conclusions:

[0165] 1. Best Example: Example 3 exhibits the best comprehensive performance, including the highest specific surface area and pore volume, the lowest CO oxidation reaction onset temperature, the highest reaction rate, the lowest apparent activation energy, and the best thermal stability and cycle performance. This may be due to its optimized Ce / Zr ratio and suitable synthesis conditions.

[0166] 2. Advantages of the core-shell structure: By comparing the examples and comparative example 1 (single Ce-MOF), we can clearly see the significant performance improvement brought by the core-shell structure. The core-shell structure not only increases the specific surface area and pore volume of the material, but also significantly reduces the reaction temperature and improves the catalytic activity and stability. This verifies the effectiveness of our core-shell structure design concept.

[0167] 3. The key role of thermal driving mechanism: Comparative Example 2 (without heat treatment) shows significantly lower catalytic activity and stability compared with the corresponding examples. The in situ XPS results more directly prove that Ce 3+ / Ce 4+ The increase in the ratio and the significant increase in the oxygen vacancy concentration are exactly the manifestation of the thermally driven mechanism we expected.

[0168] 4. Synergistic effect of Ce and Zr: By adjusting the Ce / Zr ratio (Comparative Example 3), we found that the appropriate Ce / Zr ratio is crucial to obtain the best performance. This shows that Ce and Zr do have a synergistic effect, which may be achieved by adjusting the electronic structure and redox properties.

[0169] 5. Importance of synthesis conditions: Comparative Examples 5 and 6 respectively verify the effects of synthesis temperature and time on material properties. Appropriate synthesis conditions are crucial to forming an ideal core-shell structure and crystal morphology, which in turn affects the catalytic performance of the material.

[0170] In addition, the present invention also exhibits some unexpected technical effects:

[0171] 1. Ultra-high thermal stability: Example 3 still maintains 98% of the initial activity after 100 hours of high-temperature reaction, which is far beyond our expectations. This may be due to the fact that the Zr-MOF shell not only provides structural stability, but also forms a dynamic protection mechanism at high temperatures, which may involve the interfacial interaction between Zr-MOF and Ce-MOF.

[0172] 2. Excellent low-temperature activity: Example 3 achieved a 50% CO conversion rate at 95°C, which is extremely rare among similar MOF catalysts. This excellent low-temperature activity may be due to the unique electron transfer mechanism and dynamic regulation of oxygen vacancies in the core-shell structure.

[0173] 3. Self-optimization of cyclic performance: Interestingly, the activity retention of some samples (such as Examples 2, 3, and 4) after cyclic testing is even slightly higher than that of long-term stability testing. This suggests that the material may have undergone some kind of self-optimization or reconstruction process during thermal cycling, further enhancing its stability.

[0174] 4. Significant increase in oxygen vacancy concentration: In-situ XPS results show that the increase in oxygen vacancy concentration after heat treatment is much greater than expected, especially the increase of up to 94.4% in Example 2. This significant increase in oxygen vacancies may be due to the synergistic effect between Ce and Zr in the core-shell structure, resulting in easier oxygen release and more active site formation.

[0175] In general, these experimental results not only validate our design concept, but also reveal some unexpected performance advantages. The high activity, high stability and excellent low-temperature performance of the thermally driven Ce / Zr core-shell MOF catalytic material provide new ideas and possibilities for the development of a new generation of efficient environmental catalysis and energy conversion materials.

[0176] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a thermally driven Ce / Zr core-shell MOF catalytic material, characterized in that: The following steps are involved: (1) Preparation of Ce-MOF core; (2) preparing a Zr-MOF shell based on the Ce-MOF core; (3) The obtained Ce / Zr core-shell MOF material is activated by heat treatment.

2. The preparation method according to claim 1, characterized in that: The step (1) comprises: First, 10-50 parts by weight of cerium (III) nitrate hexahydrate and 5-25 parts by weight of 1,3,5-benzenetricarboxylic acid are dissolved in 200-400 parts by weight of N,N-dimethylformamide; Secondly, the resulting mixture is reacted at 140-180° C. for 12-48 hours; Then, it was cooled to room temperature and the product was collected by centrifugation; Again, wash with N,N-dimethylformamide and anhydrous ethanol three times respectively; Finally, the Ce-MOF core material was obtained by vacuum drying at 60-80 °C for 12-24 h.

3. The preparation method according to claim 1, characterized in that: The step (2) comprises: First, 5-25 parts by weight of zirconium (IV) chloride and 3-15 parts by weight of terephthalic acid are dissolved in 100-200 parts by weight of N,N-dimethylformamide and 10-30 parts by weight of glacial acetic acid; Secondly, adding 10-50 parts by weight of Ce-MOF core material to the obtained mixture; Then, the resulting mixture is reacted at 120-160° C. for 24-72 hours; Again, cool to room temperature and collect the product by centrifugation; Finally, the mixture was washed with N,N-dimethylformamide and anhydrous ethanol for three times respectively and vacuum dried at 60-80°C for 12-24 hours to obtain the Ce / Zr core-shell MOF material.

4. The preparation method according to claim 1, characterized in that: The step (3) comprises: The obtained Ce / Zr core-shell MOF material was placed in a tubular furnace, and heated to 300-500°C at a heating rate of 2-5°C / min under a nitrogen atmosphere, maintained for 2-6 hours, and then naturally cooled to room temperature.

5. A thermally driven Ce / Zr core-shell MOF catalytic material prepared according to the preparation method of any one of claims 1 to 4.

6. The thermally driven Ce / Zr core-shell MOF catalytic material according to claim 5, characterized in that: The Ce-MOF core is prepared by reacting cerium (III) nitrate hexahydrate and 1,3,5-benzenetricarboxylic acid.

7. The thermally driven Ce / Zr core-shell MOF catalytic material according to claim 5, characterized in that: The Zr-MOF shell is prepared by reacting zirconium (IV) chloride and terephthalic acid.

8. The thermally driven Ce / Zr core-shell MOF catalytic material according to claim 5, characterized in that: The material has a core-shell structure, in which Ce-MOF serves as the core and Zr-MOF serves as the shell.

9. The thermally driven Ce / Zr core-shell MOF catalytic material according to claim 5, characterized in that: The material is activated by heat treatment at 300-500° C. for 2-6 hours.

10. Use of the thermally driven Ce / Zr core-shell MOF catalytic material according to any one of claims 5 to 9 in environmental catalysis, energy conversion or selective oxidation reaction.